Genetically Predicted Causality of 28 Gut Microbiome Families and Type 2 Diabetes Mellitus Risk - Xiang, Kun; Zhang, Jing-Jing; Xu, Yuan-Yuan; Zhong, Xing; Ni, Jing; Pan, Hai-Feng (Frontiers in Endocrinology, 2022)
Mounting evidence indicates that gut microbiome may be involved in the pathogenesis of type 2 diabetes mellitus (T2DM). However, there is no consensus on whether there is a causal link between gut microbiome and T2DM risk. In the present study, the Mendelian randomization (MR) analysis was performed to investigate whether gut microbiome was causally linked to T2DM risk. The single nucleotide polymorphisms (SNPs) that were significantly related to exposure from published available genome-wide association study (GWAS) were selected as instrumental variables (IVs). The robust methods including inverse variance weighting (IVW), MR Egger and weighted median were conducted to infer the causal links. Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) and MR-Egger regression were used to test whether there was horizontal pleiotropy and identify outlier SNPs. The estimates of IVW suggested that Streptococcaceae (odds ratio (OR)=1.17, 95% confidence interval (CI), 1.04-1.31, P=0.009) was associated with higher risk of T2DM in European. In Asian population, the MR IVW estimates revealed that there was a causal link between Acidaminococcaceae and T2DM risk (OR=1.17, 95% CI, 1.04-1.31, P=0.008). There was no evidence of notable heterogeneity and horizontal pleiotropy. However, after false discovery rate (FDR) correction, the causal link between gut microbiome and T2DM was absent (FDR P>0.05). In summary, using genetic instruments, this study does not find evidence of association between the 28 gut microbiome families and T2DM risk. However, Streptococcaceae and Acidaminococcaceae may have a borderline positive correlation with T2DM risk.